Transformação institucional do Ministério Público: da defesa do estado à defesa da sociedade - NORONHA FILHO, Vicente de Paulo Tavares (Universidade Federal do Pará, 2017)
This work elucidated the institutional transformation of the Brazilian Public Ministry (MPB), more specifically the Federal Public Ministry (MPF). The problem guiding this research was: Under what circumstances was the transformation of the Brazilian Public Ministry of the State defender to defender of society. To achieve these goals bibliographic and empirical research has been done around the history and development of the Federal Public Ministry. At the end we concluded that the historical order and socio- political factors were essential for the course of Brazilian democracy emerged a new institution empowered and entitled to the filing of civil lawsuits, which transformed this institution Republican core combat patrimonialism and misconduct administrative in Brazil.